Relying on others an essay in epistemology - Goldberg, Sanford, 1967- (Oxford : Oxford University Press, 2010)
Sanford Goldberg examines the role that others play in our attempts to acquire knowledge of the world: through what they say or through their salient silences. He argues that this sort of knowledge poses a challenge to some cherished 'individualistic' assumptions in traditional theories of knowledge.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Knowledge, Theory of